The Strategy Of The Metro City Government In Improving The Effectiveness Of Subsidized LPG Distribution: Challenges, Solutions, And Innovations - Rahmadian, Isna; Mustaghfiroh, Siti; Firmansyah, Firmansyah (Fakultas Hukum Dehasen, 2025)
Liquefied Petroleum Gas (LPG) is a household fuel that is highly sought after due to its affordability and accessibility. However, the distribution of subsidized LPG often misses its target, leading to inequality. This study aims to analyze the effectiveness of subsidized LPG distribution policies in Kota Metro and identify strategies to improve target accuracy. Using a qualitative research method through field studies and a normative-juridical approach, data was collected from interviews, observations, and documentation involving various LPG user groups, including upper-middle-class, lower-middle-class communities, and LPG depot managers. The findings reveal the need for a transformation in subsidy policies to an individual-based approach and stricter distribution oversight to ensure that subsidized LPG reaches and benefits the poor and vulnerable communities.